COVID-19 and mental health: Building back better or reimagining a new way forward? - Mark Tomlinson; Marguerite Marlow (PLoS Medicine, 2023)
In this Perspective, Mark Tomlinson and Marguerite Marlow argue that equitable improvements in mental health outcomes cannot be achieved without first dismantling colonial and paternalistic approaches to global mental health.